PENDAMPINGAN LAPORAN KAS YAYASAN CEMPAKA EDUCATION CENTERDILERENG GUNUNG ARJUNA - Lusy, Lusy; Widyastuti, Maria (Jurnal Abdimas Musi Charitas, 2022)
The community service carried out takes the object of stakeholders from the Cempaka EducationCenter Foundation, which is located at Jl. Indokilo RT. 07, RW. 02, Gamoh Hamlet, DayurejoVillage, Prigen District, East Java. Based on the social analysis conducted through theobservation and interview stages, it was found that they were unable to find the right way ofrecording cash disbursements, especially if someone took the money first without bringingevidence in the form of a note. The implementation of this activity is carried out using aparticipatory method in the form of mentoring which requires a commitment from each member torealize independence and sustainability in the implementation of activities. Mentoring activitiesare divided into two stages, namely: (1) the design stage of the temporary bill; and (2) theimplementation phase of the temporary bill form. In the implementation phase there is also anevaluation through feedback from the stakeholders of the Cempaka Education Center Foundationregarding the format of the temporary bill that has been designed. This activity has limited timedue to the Implementation of Community Activity Restrictions (PPKM) caused by the Covid-19Pandemic. The activity plan for the first phase has been 100% implemented, it is hoped that in thefuture it can be continued with other Financial Report assistance needed by stakeholders of theCempaka Education Center Foundation.